JUVENILE IDIOPATHIC ARTHRITIS (Academicia Globe: Inderscience Research, 2023)
Juvenile idiopathic (rheumatoid) arthritis (JIA) is a chronic, severe progressive disease of children and adolescents with a predominant lesion of the joints of unknown etiology and complex, autoimmune pathogenesis, which leads to gradual destruction of the joints, is often accompanied by extra-articular manifestations, disrupts the growth and development of the child, and negatively affects the quality of life [2]. Juvenile rheumatoid arthritis remains the most commonly detected disease in childhood Rheumatology. It is accompanied by total damage to connective tissues, which leads to a narrowing of the joint space, the formation of erosive areas on the surface of the joints, atrophic changes in muscle fibers.Basically treat juvenile rheumatoid arthritis in children of different ages in specialized medical institutions or special departments of public hospitals, where specialized doctors work, there is the necessary diagnostic and therapeutic equipment. Childhood juvenile rheumatoid arthritis is a rapidly progressive inflammatory disease in which children and adolescents under 16 years of age affect the joints.